Participants' perception on the effectiveness of non-lecture methodology in a team building training program - Mohd Salleh, Mohd Fuad (1998)
The effectiveness of a training program is a critical issue faced by all organizations and training provider. This issue is concerned with the effectiveness of a training transfer which constitute three major aspect, knowledge, skills, and attitudes. Participants perception is part of the factors in contributing towards the effectiveness of a training program. Thus, it must be taken into consideration when conducting any evaluation on the effectiveness of a training program. This study was aimed towards describing participants' perceptions on the effectiveness of a Team Building program that was conducted through series of non-lecture activities at Sabha Total Training Center. The objectives of the study are: (1) to understand the participants' demographic characteristics; (2) to determine the learning abilities (change in skills, knowledge, and attitude after attending Team Building training program); (3) to compare the effectiveness between lecture and games (training methodology) in team building program; and (4) to find out the participants' reaction towards team building training program. One hundred questionnaires were sent out to participants in two organizations that were willing to participate in the study. Participants were asked to rate the questionnaires constitute of demographic questions, questions on reaction towards the training program, questions on skills, knowledge, and attitude towards team building program, and questions on comparison between lecture and games effectiveness in a team building program. Data were gathered, coded and then analyzed using Statistical Package for Social Science (SPSS). Frequencies, mean, median, and percentage were used in the analysis.